18F‐FDG PET/CT in early phase of sporadic Creutzfeldt‐Jacob disease: A case report - Giovanni Boero; Filippo Lauriero; Donato Fusillo; Rosa Calvello; Antonia Cianciulli; Maria Antonietta Panaro; Piergianni Moda (Clinical Case Reports, 2024)
Key Clinical Message Creutzfeldt–Jakob disease is a neurodegenerative disorder caused by brain accumulation of a misfolded form of the cellular prion protein, whose diagnosis is challenging, particularly in early stages, due to the variability and nonspecificity of the clinical and radiological features. 18F‐fluorodeoxyglucose positron‐emitted tomography has the potential to be considered a crucial investigation in these patients, revealing metabolic abnormalities earlier than the conventional neuroimaging analysis. Abstract A 59‐year‐old man, the military officer, was referred to our Units for the onset of neurological symptoms rapidly evolving within a month, characterized by akinetic mutism, constructional apraxia, and disorders of spatial orientation. Brain 18F‐fluorodeoxyglucose (18F‐FDG) positron‐emitted tomography (PET)/CT depicted an asymmetric hypometabolism in the left fronto‐temporo‐parietal cortex, as well as in the left thalamus and the right cerebellar hemisphere, while the glucose metabolism appears to be preserved in the somatosensory cortex and the basal ganglia. Laboratory routine analyses, cerebrospinal fluid routine, infective tests, electroencephalography (EEG), and brain magnetic resonance (MR) were all unremarkable. A positive RT‐QuIC result on cerebro‐spinal fluid (CSF) was subsequently shown, without any pathogenic gene mutations and, therefore, the result was consistent with a diagnosis of sporadic Creutzfeld–Jacob disease. The clinical evolution was quickly unfavorable, and the patient died about 4 months after hospital admission. FDG PET/computed tomography (CT) has the potential to be considered a crucial investigation in these patients, documenting metabolic changes long time before other diagnostic investigations such as CSF, EEG, brain CT, and brain MR, thus suggesting a greater sensitivity of glucose metabolic evaluation in the early stage of the disease in question.